Por uma história social do fazer científico: o ensino de história e a história da ciência no IFRN - Jorge, Vicente Amintas (2020)
This work intends to favor an approximation of Science with its history. But it is not restricted to that. It also conducts an analysis of the relevance and importance of science education in a contextualized way in time and space. From a qualitative research, an image was acquired, as faithful as possible, of the way science is viewed and worked within the educational institute in which the author teaches, IFRN, more specifically on the campus where I work, Campus Santa Cruz -RN and in the degree courses offered by the same (Degree in Physics and Mathematics). From such research, a characteristic science view was obtained that guided this work in the construction of a transforming action: the elaboration of a History of Science curricular subject to be proposed to the institute as an elective subject of these courses. These actions intend, as stated at the beginning of this summary, a necessary and very useful approximation of scientific knowledge with its historicity, because only then will we have a more human, closer and more reflective teaching of science.